Composites on the basis of Y2O3 submicron spheres functionalized with nanosize titania: preparation and characterization - N. A. Dulina; L. N. Obolenskaya; A. V. Tolmachev; O. M. Vovk; E. V. Savinkina; G. M. Kuzmicheva; N. V. Sadovskaya; N. A. Prokudina (Тонкие химические технологии, 2012)
Composites anatase/Y2O3, η-TiO2/Y2O3, Degussa P25/Y2O3 and Hombifine/Y2O3 were prepared by simultaneous dispersion of Y2O3 and TiO2 powders in weakly alkaline aqueous media or dispersion of Y2O3 powders in acidic titania-containing hydrosols followed by special treatment. Initial reagents and composites were characterized by X-ray diffraction, IR spectroscopy, transmission and scanning electronic microscopy with X-ray spectral microanalysis.